Strengthening social media capabilities to improve private Islamic higher education marketing performance - Riofita, Hendra; Dimasadra, Waldana (Faculty of Business & Economics, Universitas Islam Indonesia, 2022)
Purpose – This research is conducted to strengthen social media capabilities to improve Private Islamic Higher Education marketing performance as well as the number of prospective students.Methodology – The design of this study is a survey. The data processed with SPSS and Amos program are collected from the elements of leaders of Indonesian private Islamic higher education. Multi-stage sampling and simple random methods are applied.Findings – Digital public relations and digital network empowerment, respectively has a very significant role to strengthen social media capabilities to improve Private Islamic Higher Education marketing performance and as well as the number of prospective students. Implications – The findings of this research encourage Private Islamic Higher Education to apply both digital public relations and digital network empowerment on social media. Originality – This research develops digital public relations and digital network empowerment as intervening variables, considering that both digital constructs have the capabilities to realize the marketing-related activities through a collaborative relationship approach required by social media to attract prospective students to join Private Islamic Higher Education.